Evidence-based geology as a basis for improving the efficiency of innovative design of the development of Tengizchevroil oil fields - Nursaule Tauova (Jurnal Pendidikan Vokasi, 2022)
The article's main purpose is to study the method of storing sulfur in solid form in a large block at Tengizshevroil deposits and dispose of sulfur residues. Thus, we have to admit that, in this case, the evaluation of the effectiveness of the innovation at the stage of its development was performed incorrectly, and thus the consumer was misled. As a rule, the production activities of enterprises are planned according to the average parameters that are not known reliably in advance and can change randomly. At the same time, a situation with sharp changes in these indicators is extremely undesirable because this means the threat of loss of control. The smaller the deviation of the indicators from the average expected value, the greater the stability. That is why the statistical method based on mathematical statistics has become the most widespread in assessing investment risk. A more complex mathematical apparatus (regression and correlation analysis, simulation modeling methods) allows for a deeper analysis of the risk and its causes. The discrepancy between modern progressive technical capabilities and archaic "expert" geological thinking. Unfortunately, when making decisions, geologists often rely solely on personal experience, while the basis of evidence-based geology is experimental research (including statistical experiments), which serves as material for a systematic review, meta-analysis, and the development of practical guidelines (recommendations) based on them. The use of the principles of evidence-based geology involves a combination of individual practical experience and optimal evidence obtained through a systematic analysis of experimental and experimental-methodical studies. The instrumental support of evidence-based geology is modern technologies of statistical data analysis, data mining and artificial intelligence, and analytical platforms to build applied solutions.